The role of mechanosensitive ion channels in the gastrointestinal tract - Yang, Haoyu; Hou, Chaofeng; Xiao, Weidong; Qiu, Yuan (Frontiers in Physiology, 2022)
Mechanosensation is essential for normal gastrointestinal (GI) function, and abnormalities in mechanosensation are associated with GI disorders. There are several mechanosensitive ion channels in the GI tract, namely transient receptor potential (TRP) channels, Piezo channels, two-pore domain potassium (K2p) channels, voltage-gated ion channels, large-conductance Ca2+-activated K+ (BKCa) channels, and the cystic fibrosis transmembrane conductance regulator (CFTR). These channels are located in many mechanosensitive intestinal cell types, namely enterochromaffin (EC) cells, interstitial cells of Cajal (ICCs), smooth muscle cells (SMCs), and intrinsic and extrinsic enteric neurons. In these cells, mechanosensitive ion channels can alter transmembrane ion currents in response to mechanical forces, through a process known as mechanoelectrical coupling. Furthermore, mechanosensitive ion channels are often associated with a variety of GI tract disorders, including irritable bowel syndrome (IBS) and GI tumors. Mechanosensitive ion channels could therefore provide a new perspective for the treatment of GI diseases. This review aims to highlight recent research advances regarding the function of mechanosensitive ion channels in the GI tract. Moreover, it outlines the potential role of mechanosensitive ion channels in related diseases, while describing the current understanding of interactions between the GI tract and mechanosensitive ion channels.